(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Marijuana is produced in almost every country in the world, which makes it the most prevalent illegal drug in the world drug market. The number of laboratories that have been discovered in Serbia in recent years is one of the potential indicators of the increasing expansion of domestic marijuana production under laboratory controlled conditions. The aim of this paper is to determine the prevalence and characteristics of illegal indoor marijuana production laboratories. The sample included 136 illegal marijuana cultivation laboratories discovered in Serbia (without Kosovo and Metohija) from 1st, January, 2013 till 30th, June, 2019. The lack of standardized reporting patterns makes it impossible to analyze the amount of seized drugs. The seized drugs were in various stages of production process and preparation for the illegal market; in some reports the seizure of whole plants of different sizes was reported; in some reports the amount of raw and/or dried drugs was expressed in kilograms. Due to the fact that the available data on cannabis production are divided, non-standardized and often scientifically unfounded, it is impossible to present the total amount of cannabis produced in Serbia precisely. The paper presents the distribution of laboratories and their basic characteristics in terms of location, production capacity, quality of equipment, number of arrested persons and the quantity of money and weapons seized.